2021
DOI: 10.3390/ijms221910413
|View full text |Cite
|
Sign up to set email alerts
|

EK100 and Antrodin C Improve Brain Amyloid Pathology in APP/PS1 Transgenic Mice by Promoting Microglial and Perivascular Clearance Pathways

Abstract: Alzheimer’s disease (AD) is characterized by the deposition of β-amyloid peptide (Aβ). There are currently no drugs that can successfully treat this disease. This study first explored the anti-inflammatory activity of seven components isolated from Antrodia cinnamonmea in BV2 cells and selected EK100 and antrodin C for in vivo research. APPswe/PS1dE9 mice were treated with EK100 and antrodin C for one month to evaluate the effect of these reagents on AD-like pathology by nesting behavior, immunohistochemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Developing animal models of human illnesses is a challenging task for translational research, but it is indispensable to understanding pathomechanism, searching for biomarkers, and engineering novel treatment [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. Migraine research is no exception.…”
Section: Animal Models Of Neurogenic Inflammationmentioning
confidence: 99%
“…Developing animal models of human illnesses is a challenging task for translational research, but it is indispensable to understanding pathomechanism, searching for biomarkers, and engineering novel treatment [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. Migraine research is no exception.…”
Section: Animal Models Of Neurogenic Inflammationmentioning
confidence: 99%
“…The residues are suspended in water before being partitioned with n-hexane and ethyl acetate. Antrodin C is isolated from the ethyl acetate fraction by subsequent chromatography on silica gel and Sephadex LH-20 columns [ 77 ]. The semipreparative HPLC may increase the purity of antrodin C. A semipreparative HPLC column (Waters XBridge C18 column, Φ19 × 250 mm 2 , 5 µm) is used to separate crude antrodin C. The mobile phase comprises distilled water H 2 O (0.5% acetic acid) and acetonitrile (34851, Sigma–Aldrich) (10 mL/min) to obtain antrodin C with a purity exceeding 95% [ 73 ].…”
Section: Isolation and Purification Of Bioactive Compounds From ...mentioning
confidence: 99%
“…Recent studies have analyzed specific natural or synthetic compounds that can modulate M1/M2 microglial polarization and suggested that they can serve as potential therapeutic agents for NDs. Furthermore, studies documenting the impact of the microbiome on microglial polarization have also been reported [47][48][49].…”
Section: Microglial Polarization As An Inflammation/anti-inflammation...mentioning
confidence: 99%